2013
DOI: 10.4103/0019-5154.108029
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-duration therapy in leprosy: Limitations and opportunities

Abstract: Leprosy has been considered a curable disease after the implementation of multidrug therapy (MDT), which has been proven to be safe and effective, by bringing about a significant change in the global and national scenario of leprosy by upgrading the control of leprosy to the next stage of eradication. Since its introduction, the MDT regimens for the treatment of leprosy have undergone several changes especially with regard to the duration of treatment. The advantages of shortened duration of treatment need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…This tendency reinforces stigma associated with the disease [ 29 ]. Besides, it is an affront to the World Health Organisation’s (WHO) encouragement for the integration of leprosy into the general health service where leprosy patients should be treated in the same outpatient department as those with any other disease [ 30 ]. This can signal to the patients and their communities that leprosy is not a 'different' disease.…”
Section: Discussionmentioning
confidence: 99%
“…This tendency reinforces stigma associated with the disease [ 29 ]. Besides, it is an affront to the World Health Organisation’s (WHO) encouragement for the integration of leprosy into the general health service where leprosy patients should be treated in the same outpatient department as those with any other disease [ 30 ]. This can signal to the patients and their communities that leprosy is not a 'different' disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the limitations associated with fixed duration MDT is the continued visibility of a clinically active patch in a proportion of patients and continued inflammatory response resulting in persistent clinical activity for up to 12-18 months. [ 21 ] In our study, 9.32% ( n = 66) of post RFT patients visited dermatologists because of lepra reactions, while 11.58% ( n = 82) patients presented due to persistent neuritis. In a study from Brazil in RFT patients, it was observed that T1R was most common in 37.1%, followed by T2R in 18.6% and neuritis in 13.9%.…”
Section: Discussionmentioning
confidence: 61%
“…The efficacy of pulse rifampicin, ofloxacin, and minocycline (ROM) as an alternative/additional regimen to treat multibacillary leprosy patients who refuse clofazimine needs to be evaluated. [ 34 ] In addition, with increasing multibacillary leprosy load in the community and severe forms of lepromatous leprosy with high initial bacillary load being diagnosed across the country, there is an urgent need to review the current guidelines of “fixed duration therapy” (FDT) for all types of multibacillary leprosy. It is also important to recognize that leprosy can be associated with other comorbidities such as tuberculosis, HIV, and diabetes which could affect clinical manifestations and complications; hence, therapeutic management strategies need to be tailored to such situations.…”
Section: Need For New Drug Regimenmentioning
confidence: 99%